DEVELOPMENT OF WORKSHEET-BASED MATHEMATICAL MODELLING USING CONTEXT OF ENERGY CONVERSION FOR GEOMETRIC SEQUENCE MATERIAL - Akhmad Sumbandari; Yusuf Hartono; Somakim Somakim (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This research is a series of developmental study design research, the prototyping stage – self-evaluation and formative evaluation. At self-evaluation stage, designing the worksheet, three development characteristics: content, constructs, and language are the concern. Then, at formative evaluation stage, the expert stage review was conducted to see the validity of the worksheet (one-to-one testing and interviews with 4 students who are part of the population based on high, medium, and low abilities). Document analysis is administered by matching the suitability of the workseheet designed on the initial prototype with the modeling framework, high school curriculum, and geometric sequences learning. Analysis of observations and interviews were carried out descriptively by observing the difficulties and findings of the process on doing the worksheet. Walk through analysis was obtained by descriptively analyzing and revising based on the validator notes. Result at the expert stage review and one-to-one showed that the worksheet based on mathematical modeling using the context of energy conversion in geometric sequences learning was valid.Penelitian ini adalah penelitian design research tipe development study menggunakan model ADDIE dan pada tahap implementasi dan evaluasi mengikuti alur formative evaluation dari Tessmer. Penelitian ini bertujuan untuk menghasilkan LKPD berbasis pemodelan matematika pada materi pola barisan geometri menggunakan konteks konversi energi yang valid, praktis, dan memiliki efek potensial. Teknik pengumpulan data terdiri dari walkthrough, observasi, wawancara, dan tes. Analisis observasi dan wawancara dilakukan secara deskriptif dengan mengamati kesulitan dan temuan dari proses pengerjaan LKPD siswa. Analisis walkthrough dilakukan dengan cara menganalisis secara deskriptif dengan merevisi berdasarkan catatan validator. tes dilakukan setelah pembelajaran untuk melihat efek potensial dari LKPD yang dikembangkan. Hasil penelitian menunjukkan bahwa LKPD yang dihasilkan telah valid, praktis, dan memiliki efek potensial terhadap kemampuan pemodelan matematika siswa. Persentase skor pada saat tes evaluasi menunjukkan 54,05 % terkategori sangat baik, 32,43% terkategori baik, dan 13 % terkategori cukup.